Perception Of Contraception Access And Utilization In Teenagers In Senior High School No 8 Denpasar, Bali - R. Listyowati; N. M. S. Nopiyani; P. A. Indrayathi (Institute for Research and Community Services Udayana University, 2017)
The images of teenagers in the world, especially in South Asia and Southeast Asia have less information about reproductive and sexual health because of the assumption that it is unnecessary even considered harmful if they knew it. It’s not surprise that the teen birth rate is still quite high. previous research in Indonesia on adolescent premarital sexual behavior, obtain a yield of about 25% - 51% of teens have sex before marriage. (Utomo ID 2009; 40 (2) :. 133-46.). Studies in Bali obtain the results of teenage boys in high school (SMA) and junior high school (SMP) more premarital sex (40.3% and 29.4%) than girls (3.6% and 12.5%). Teenage boys in Bali more permissive toward premarital sexual behavior than girls and about 5% of teens have sex before marriage (Faturochman 1992; 1 :. 12-7) Adolescents have a right to a healthy life. They need to have access of the tools that can protect their health, such as condoms, contraception and youth-friendly health services are comprehensive. Governed by Law no. 36/2009 Article 4 and 5, which states that everyone has the same right to gain access of health and this rule does not see marital status. The purpose of this study was to describe the general perception of access and use of contraception among adolescents in the city of Denpasar.